Élite sport & employability: Theoretical frameworks, policies and educational perspectives - Sergio Bellantonio; Domenico Tafuri (Formare, 2019)
Increasing emphasis on the importance of adult education programs in European agenda has led to a focus on the employability of élite athletes too. In the field of sport studies, there has been little research into the relationship between élite sport and employability. This paper wants to reflect on the nature of sports and training paths today from an educational perspective and the possible implications for the development of best practices within this context of life and experience. A new approach on sport and education is necessary, based both on learning outcomes and evidence-based strategies which will lead to the best possible match between the needs of society and requirements of the job market, even in sport.